Investigating the performance of “Smart Probe” based indirect EMI technique for strength development monitoring of cementitious materials-modelling and parametric study - Lu, Xubin (2020)
Electromechanical impedance (EMI) technique has been proven effective in strength development monitoring of early age cementitious materials with the aid of statistical tools. The critical limitation of this technique lies in that no parametric evaluation of the cementitious material can be provided. This is partially due to the inconsistency of the baseline of the measured impedance signatures. The recently developed Smart Probe based indirect EMI technique overcomes the abovementioned drawbacks of this technique, enabling parametric estimation of the cementitious material being monitored. The influence of various physical parameters of the Smart Probe on its performance in curing monitoring of cementitious material has not been investigated. In this study, the analytical model of the Smart Probe previously proposed by the authors is improved. In the improved model, the distributed stiffness and mass of the embedded segment of the Smart Probe are explicitly formulated in the governing equations of motion, allowing more realistic predictions of the actual dynamic features of the Smart Probe-cementitious material system. A 3-D coupled field finite element (FE) model is also established to predict the admittance spectrum of the Smart Probe embedded in cementitious material. It is found that multiple resonance peaks in the conductance spectrum computed by FE simulation are in good agreement with the experimental data in terms of resonance frequency. The resonance peaks predicted by both the FE and the analytical models exhibit the same trend of movement as the experiment throughout the curing process, which verifies the effectiveness of the proposed models in monitoring the strength development process of cementitious materials. Parametric study conducted on the Smart Probe shows that the effect of the Poisson's ratio of the cementitious material on the resonance frequency is limited when compared with that of the dynamic modulus. It is also found that the dimensions and position of the PZT patch influence the magnitude and the sharpness of the resonance peaks in the admittance spectrum. The improved analytical model can be a useful tool for optimizing the design of Smart Probes for monitoring purpose.